2008
DOI: 10.1111/j.1745-9125.2008.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Neighborhood Danger, and Risk‐avoidance Strategies Among Urban African‐american Youths*

Abstract: Research consistently reveals that fear of crime and perceived risk are demographically and ecologically patterned. Women and individuals in disadvantaged community settings report increased fear and perceptions of risk. For women, these fears and perceptions are tied to concerns about sexual violence specifically, whereas for individuals in distressed neighborhoods, crime rates, “incivilities,” and poor police‐community relations are often identified as important correlates. Here, we build from the insights o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
188
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(206 citation statements)
references
References 66 publications
14
188
3
1
Order By: Relevance
“…8 Our findings differ from work that uncovered gender differences in risk-management strategies among teenagers in violent neighborhoods (Cobbina et al 2008). The difference may be due to age grading.…”
Section: Notescontrasting
confidence: 56%
See 1 more Smart Citation
“…8 Our findings differ from work that uncovered gender differences in risk-management strategies among teenagers in violent neighborhoods (Cobbina et al 2008). The difference may be due to age grading.…”
Section: Notescontrasting
confidence: 56%
“…Some have reported similar findings among nongang members. Cobbina, Miller, and Brunson (2008) found that young black women in St. Louis relied on male friends and kin for protection when they ventured beyond their neighborhood. Harding (2010:72) found that black adolescent boys in Boston respond to violent, interneighborhood rivalries by fashioning ties with older, nonkin males within their neighborhoods.…”
Section: Friendship Formation Among Childrenmentioning
confidence: 99%
“…The racial differences could be attributed to differences in women's responses to the urban, often crime-ridden environment of disadvantaged neighborhoods. Research suggests that women of color respond to disadvantage and crime in the inner city by retreating from community life (Cobbina, Miller, & Brunson, 2008). Further, there is ample research to suggest that gender, race, and social location can affect criminal justice decision-making (Steffensmeier, Kramer, & Streifel, 1993;Steffensmeier, Ulmer, & Kramer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the conferring of a fatalistic outlook may also be intertwined with an overarching desire to appear masculine and illustrate nerve in the face of danger (i.e., violence and victimization), often prolific within urban minority male samples (Anderson 1994;Brezina et al 2009;Cobbina et al 2008;Hindelang et al 1978;Jacobs and Wright 2006;Van Dijk 1986). This finding raises further questions about whether prolonged exposure to violence may weaken or desensitize the potential effect(s) that victimization experiences may have on subsequent behavior and management of lifestyle risks.…”
Section: Discussionmentioning
confidence: 99%